2013
DOI: 10.1007/s00586-013-2794-5
|View full text |Cite
|
Sign up to set email alerts
|

Severe sprains of the sub-axial cervical spine in adolescents: a diagnostic and therapeutic challenge

Abstract: We report three cases of adolescents with severe cervical sprains at the C2-C3 level and argue the integrity of PLL as a determinant factor in the sagittal stability of the C spine in this age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…However, flexion-distraction injuries without bone fracture are not common at C2-C3 (Jubert et al 2013). A clinical study reported a few cases of "flexion sprain" at C2-C3 in adolescents causing important post-traumatic dynamic instability: antero-posterior translation of 4 to 4.5 mm and C2-C3 rotation flexion of 13 to 15 degrees measured on dynamic flexion-extension X-Rays (McLoughlin et al 2014). These results are similar to what we observed at C2-C3 (antero-posterior translations of 4 and 9 mm and local ROM ranging from 8.6 to 19.4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, flexion-distraction injuries without bone fracture are not common at C2-C3 (Jubert et al 2013). A clinical study reported a few cases of "flexion sprain" at C2-C3 in adolescents causing important post-traumatic dynamic instability: antero-posterior translation of 4 to 4.5 mm and C2-C3 rotation flexion of 13 to 15 degrees measured on dynamic flexion-extension X-Rays (McLoughlin et al 2014). These results are similar to what we observed at C2-C3 (antero-posterior translations of 4 and 9 mm and local ROM ranging from 8.6 to 19.4).…”
Section: Discussionmentioning
confidence: 99%
“…At complete disc rupture, this high anterior displacement combined with high local rotation lead to an important change in the antero-posterior position of the C2-C3 facets. This could lead to luxation and compression of the spinal cord (McLoughlin et al 2014). This phenomenon was observed for a non-traumatic flexion moment (2 Nm) which shows the importance of post-traumatic immobilization in comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Sprains to the subaxial cervical spine in adolescents have been reported from our institution previously. McLoughlin et al [5] demonstrated that it is possible to have a severe sprain of the C-spine in an adolescent, causing significant C-spine instability with an intact PLL and annulus at the injured level. Therefore, PLL integrity in an adolescent spine does not indicate stability.…”
Section: Discussionmentioning
confidence: 99%